Adopting CAQDAS in Algerian EFL Research: Barriers, Challenges, and the Need for Professional Development - Radia BOUGUEBS; Leila DJOUIMA (Langues & Cultures)
Qualitative Data Analysis (QDA) involves interpreting qualitative data (e.g., texts, interviews, recordings) to generate insights. However, QDA poses significant challenges for researchers. Computer-Assisted Qualitative Data Analysis Software (CAQDAS) has emerged to streamline these tasks. This study investigates Algerian EFL researchers' awareness of CAQDAS and its application in QDA. An online survey of 35 Algerian university researchers explored their familiarity with CAQDAS and the barriers to its use. Results indicated that while participants acknowledged CAQDAS's potential, most had never used it. Key obstacles included limited knowledge of the software, insufficient technical skills, and inadequate institutional funding. The findings suggest an urgent call for targeted professional development programs to improve researchers' CAQDAS proficiency. Such initiatives could address the gap between recognizing the software's benefits and its practical implementation in research contexts.